Data Preparations for a New Australian Gravimetric Geoid - Featherstone, Will; Kearsley, A.; Gilliland, J. (The Institution of Surveyors, Australia Inc., 1997)
The rationale is given for a new determination of the Australian gravimetric geoid. In preparation for this task, the Australian Geological Survey Organisation's gravity data base has been validated and reformatted. Additional information in the form of digital terrain data are available from the Australian Surveying and Land Information Group's 9" by 9" Digital Elevation Model (DEM), derived from ~5.2 million spot elevations and the ~0.6 million elevations in the gravity data base. Both gravity and terrain data were transformed to give their horizontal position on the GRS80 ellipsoid, which produces a homogeneous data source for subsequent geoid computations. The gravity anomalies were computed using a second-order, free-air correction and normal gravity was computed using GRS80 latitude. Satellite altimeter-derived gravity anomalies are also considered as an additional source of information in offshore areas. The statistical fit of the new EGM96 global geopotential model to geometrical control provided by the Australian Fiducial and National GPS Networks is shown to be an improvement upon the OSU91A model, upon which AUSGEOID93 was based.